OBTAINING ACTIVATED CARBON FROM A COCONUT SHELL CARBONIZED - Chumpitaz R., O. M. (2013)
In adsorption and porous solids laboratory of the National Center of Scientific Research Centre (CNIC) have been obtained activated carbon from different national row materials for their use in the -protection of the environment, mainly in the adsorption of polluting gases of the atmosphere. In the present work preliminary results on the obtaining of coal activated starting from charred of coconut shell in a horizontal tubular oven with dry nitrogen as well as mixed with vapour of water as inert gas and activation temperatures of 773, 873, 973, 1073 K, are exposed. For !he evaluation of !he adsorbing features the Dubinin Theory of the micropore volume was applied to the adsorption of different vapors like the NH3 and the C02. The micropores volumes and the characteristic energy of the adsorption are determined and the products are compared to determine the besT conditions in obtaining the activated carbons.